Reworking and discontinuities in Holocene sedimentation in the Nile Delta: Documentation from amino acid racemization and stable isotopes in mollusk shells - Goodfriend, G. A.; Stanley, D. J. (Marine Geology, 1996)
The late Holocene sedimentary history of the northwestern edge of the Nile Delta is reconstructed from amino acid racemization, radiocarbon, and stable isotope analysis of a series of bivalve shells from a core taken at the edge of Lake Maryut near Alexandria. Amino acid racemization, confirmed by radiocarbon and stable isotope analysis, indicates that in many parts of the core mixed-age mollusk assemblages are present. Dating of the time of sediment accumulation at various levels in the core is therefore based on the age of the youngest shells, which are identified by amino acid racemization analysis (lowest D/L values). AMS radiocarbon analysis is used to determine the ages of the shells, except for the most recent sediments (last 100 yr), for which aspartic acid racemization provides more precise ages.Amino acid racemization analysis of 59 shells from 21 levels in the 4.8 m Holocene sequence in the core enabled identification of a large hiatus. Holocene sedimentation started at ca. 2400 BC, apparently corresponding to a westward shift of the course of the Canopic Nile distributary which lies to the east. Deposition continued at a rate of 1.4 mm per year, ceasing at ca. 550 BC, at which time the Canopic Nile shifted eastward again and subsequently became defunct. A marine connection during this period is indicated by stable isotope values of shells. Sediment accumulation began again only at the end of the 19th century, when a series of irrigation canals was connected to the Lake Maryut basin. Stable isotope values indicate a strong freshwater influence. Deposition has continued to the present at a very high rate (19 mm per year) due to supply of sediments by agricultural activity.The relative ease with which racemization analyses can be carried out permits detailed analysis of core chronostratigraphy, leading to more accurate reconstruction of core chronology: hiatuses can be pinpointed and documented, and age mixtures can be identified, with appropriate individual shells being selected for AMS radiocarbon analysis. Aspartic acid racemization analysis permits dating of samples from the last several hundred years, a period for which radiocarbon analyses provide poor precision.
Tv774Times Cited:35Cited References Count:30